2017
DOI: 10.3389/fpls.2017.01547
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Barley Grains Subjected to Water Stress: To Explain the Genotypic Difference in Drought-Induced Impacts on Malting Quality

Abstract: Grain weight and protein content will be reduced and increased, respectively, when barley is subjected to water stress after anthesis, consequently deteriorating the malt quality. However, such adverse impact of water stress differs greatly among barley genotypes. In this study, two Tibetan wild barley accessions and two cultivated varieties differing in water stress tolerance were used to investigate the genotypic difference in metabolic profiles during grain-filling stage under drought condition. Totally, 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 81 publications
3
38
0
1
Order By: Relevance
“…l -asparagine is well-known to be located at the beginning of the aspartate biosynthetic pathway, thus its upregulation may be indicative of activation of the aspartate biosynthetic pathway in Rhodiola crenulata, which is consistent with upregulation of l -(+)-lysine and l -isoleucine, which are the downstream products of this pathway. Reports have shown that lysine helps improve plant drought tolerance [ 25 ] and isoleucine is closely related to plant resistance to salt stress [ 26 ] and the growth of germinating embryos [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…l -asparagine is well-known to be located at the beginning of the aspartate biosynthetic pathway, thus its upregulation may be indicative of activation of the aspartate biosynthetic pathway in Rhodiola crenulata, which is consistent with upregulation of l -(+)-lysine and l -isoleucine, which are the downstream products of this pathway. Reports have shown that lysine helps improve plant drought tolerance [ 25 ] and isoleucine is closely related to plant resistance to salt stress [ 26 ] and the growth of germinating embryos [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrates have also been reported as major osmolytes in barley [ 7 ], especially sucrose and malate [ 33 , 55 ] and some others such as ribose and 1-kestose [ 6 ]. We reported a strong increase in the levels of total soluble sugars, but no correlation was found with the relative stress tolerance of genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Munns et al [ 1 ] highlighted that barley is the most salt tolerant cereal, and its tolerance to drought or biotic stresses such as fungal disease is well-known [ 2 ]. There is a plethora of information on barley’s responses to abiotic stress, including recent studies and review articles on physiological, biochemical [ 2 , 3 , 4 , 5 ], metabolomics [ 6 , 7 ] and transcriptomics [ 8 , 9 , 10 , 11 ] aspects. Being an annual diploid plant species, with a small number of chromosomes (2 n = 14) and a huge range of genetic variability that accounts for different levels of stress tolerance, barley is a model species among crops for deciphering stress tolerance mechanisms, and hence has been subjected to many genetic studies in relation to stress tolerance, ranging from genetic variability analysis [ 12 , 13 ] to marker assisted selection in conjunction with the use of quantitative trait loci (QTLs) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the case in Mediterranean and Southeastern European environments where small grain cereals usually mature under terminal drought conditions. Studies showed that yield components and protein content (PC) decreased and increased, respectively, when barley was subjected to water stress after anthesis (Samarah et al, 2009;Wu et al, 2017). Dry matter for grain filling is a result of a post-anthesis photosynthetic activity and remobilization of storage reserves deposited prior to anthesis.…”
Section: Introductionmentioning
confidence: 99%